A study on frictional behavior of PMMA against FDTS coated silicon as a function of load, velocity and temperature. (October 2016) - Saha, Biswajit; Toh, Wei Quan; Liu, Erjia; Tor, Shu Beng; Lee, Junghoon
Abstract: Rapid developments of soft polymeric materials have inspired for a better understanding of their tribological characteristics. The tribological behavior of polymethylmethacrylate (PMMA) against 1H, 1H, 2H, 2H-perfluorodecyltrichlorosilane [CF3 (CF2 )7 (CH2 )2 SiCl3 ] (FDTS) coated silicon (Si) substrate (F-Si) as a function of the applied-temperature, load and sliding velocity was studied and reported in this paper. It was observed that friction coefficient vs. applied-temperature curves follow the viscoelastic behavior of PMMA, which indicates that molecular relaxation of PMMA is the dominating factor of its tribological properties at temperature below its glass transition temperature ( T g ). Furthermore, consistent shifts of friction coefficient vs. temperature curves toward low temperatures with increase in load in addition to sliding velocity further signified, the importance of friction induced-temperature on the tribological properties of PMMA. Highlights: Frictional behavior of PMMA against FDTS coated Si wafer was investigated. Co-relations of friction coefficient with load and velocity were established. Friction induced temperature was estimated. Effect of friction induced temperature on tribological behavior of PMMA was studied.